Ultrasonic Guided Waves in Piezoelectric Layered Composite with Different Interfacial Properties - Xiao Chen (Advances in Materials Science and Engineering)
Combining the propagation model of guided waves in a multilayered piezoelectric composite with the interfacial model of rigid, slip, and weak interfaces, the generalized dispersion characteristic equations of guided waves propagating in a piezoelectric layered composite with different interfacial properties are derived. The effects of the slip, weak, and delamination interfaces in different depths on the dispersion properties of the lowest-order mode ultrasonic guided wave are analyzed. The theory would be used to characterize the interfacial properties of piezoelectric layered composite nondestructively.